Centromere proteins CENP-C and CAL1 functionally interact in meiosis for centromere clustering, pairing, and chromosome segregation. - Unhavaithaya, Y.; Orr-Weaver, T.L. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Meiotic chromosome segregation involves pairing and segregation of homologous chromosomes in the first division and segregation of sister chromatids in the second division. Although it is known that the centromere and kinetochore are responsible for chromosome movement in meiosis as in mitosis, potential specialized meiotic functions are being uncovered. Centromere pairing early in meiosis I, even between nonhomologous chromosomes, and clustering of centromeres can promote proper homolog associations in meiosis I in yeast, plants, and Drosophila. It was not known, however, whether centromere proteins are required for this clustering. We exploited Drosophila mutants for the centromere proteins centromere protein-C (CENP-C) and chromosome alignment 1 (CAL1) to demonstrate that a functional centromere is needed for centromere clustering and pairing. The cenp-C and cal1 mutations result in C-terminal truncations, removing the domains through which these two proteins interact. The mutants show striking genetic interactions, failing to complement as double heterozygotes, resulting in disrupted centromere clustering and meiotic nondisjunction. The cluster of meiotic centromeres localizes to the nucleolus, and this association requires centromere function. In Drosophila, synaptonemal complex (SC) formation can initiate from the centromere, and the SC is retained at the centromere after it disassembles from the chromosome arms. Although functional CENP-C and CAL1 are dispensable for assembly of the SC, they are required for subsequent retention of the SC at the centromere. These results show that integral centromere proteins are required for nuclear position and intercentromere associations in meiosis.